Clay Mineral Characteristics of the Damar Formation in the Southern Part of the Coastal Area of Semarang and Kendal, Central Java - Wafid A.N., Muhammad; Zajuli, Moh. Heri Hermiyanto; Suyono, Suyono; W, Hermawan; Irzon, Ronaldo (Pusat Survei Geologi, 2025)
The study area is located in the southern part of the Coastal area of Semarang and Kendal, Central Java. The fine-grained sedimentary rocks of Damar Formation comprise tuffaceous mudstones, volcanic breccias, sandstones, tuffs and conglomerates; with occasional lava deposits and volcanic materials within alluvial fan deposits. The purpose of this study is to provide data on the characteristics of fine-grained sedimentary rocks of the Damar Formation including physical characteristics, diagenesis processes, and their implications for the history of rock accumulation. Based on Scanning Electron Microscope (SEM) analysis of four claystone samples from the Damar Formation consist of illite (K1-1.5 Al4 (Si7 6.5 Al1-1.5 O20 )(OH)4 , mixed illite (K1-1.5 Al4 (Si7-6.5 Al1-1.5 O20 ) (OH)4 - smectite (1/2Ca)0.7 (Al,Mg,Fe)4 (Si,Al)8 O20 ).nH2 O and kaolinite (Al4 (Si4 O10 )(OH)8 . Other minerals include silica or quartz fractions and feldspar. Kaolinite is the most prominent clay mineral identified in all claystone samples analysed, although the clay textures seem to be irregular shapes of Damar Formation has undergone a diagenetic process within a mesodiagenetic level indicating sediment burial at depths of 2,500–4,000 m by temperature ranging from 80° to 120°C. Keywords: Damar Formation, SEM, diagenesis, clay mineral, illite Abstrak Area studi terletak di bagian selatan pantai Semarang dan Kendal, Jawa Tengah. Sedimen berbutir halus dari Formasi Damar terdiri dari batulumpur tufaan, breksi vulkanik, batupasir, tuf, dan konglomerat, dengan setempat deposit lava dan material volkanik dengan endapan kipas aluvial. Tujuan dari studi ini adalah untuk menyediakan data terkait karakteristik dari batuan sedimen berbutir halus dari formasi Damar termasuk karakter fisik, proses diagenesis, dan implikasinya untuk sejarah akumulasi batuan. Berdasarakan Mikroskop Scanning Elektron (SEM) analisis dari 4 (empat) percontoh batulempung Formasi Damar terdiri dari illit (K1-1.5 Al4 (Si7-6.5 Al1-1.5 O20 ) (OH)4 , campuran illit (K1-1.5 Al4 (Si7-6.5 Al1-1.5 O20 )(OH)4 - smektit (1/2Ca)0.7 (Al,Mg,Fe)4 (Si,Al)8 O20 ).nH2 O dan kaolinit (Al4 (Si4 O10 )(OH)8 . Mineral lainnya adalah silika atau kuarsa berupa fraksi, felspar. Mineral lempung kaolinit merupakan mineral lempung yang paling menonjol dari analisis batu lempung, meskipun tekstur lempungnya berbentuk kurang teratur yang menandakan proses diagenesis pada level mesodiagenesis yang pernah terpendam sampai 2500 – 4000 meter dengan temperatur berkisar 80o – 120o. Kata kunci: Formasi Damar, SEM, diagenesis, mineral lempung, illit